Planning of production capacities of a high-tech enterprise based on the mathematical model of the Pontryagin maximum - A. A. Sazonov (Управление)
The article considers the method of planning the production capacity of a high-tech enterprise based on the application of the Pontryagin maximum mathematical model. The presented method is aimed at increasing the productivity of the equipment installed at the enterprise, in order to optimize the time spent and the volume of products produced. The study analyses the activities of research and production enterprise in order to improve the level of efficiency of production capacity management. The purpose of the research is to organize an effective process of planning production capacities of a high-tech enterprise based on the application of the Pontryagin maximum mathematical model, which allows you significantly to increase not only equipment performance indicators, but also optimize the time required to complete the current production program. The author tested the algorithms, models and methods proposed in the article at a research and production enterprise engaged in the production of high-tech products. The use of the obtained models will allow you to optimize peak loads in the current production program at the enterprise, reduce the labor intensity indicators in the annual production plan, determine the necessary amount of production equipment, which will eventually reduce the amount of necessary investments. The paper gives a practical example of the organization of a new type of production aimed at manufacturing various parts of complex shape.